FIGURATIVE LANGUAGE FOUN DIN CELINE DION ALBUM “FALLING IN TO YOU” BY CELINE DION - Yasimani Laia (Universitas Nias Raya, 2026)
This articel describes the kinds of figurative language in songs lyrics by The Figurative Languange Found in Celina Dion Album “Falling in to You” By Celina Dion. Language is one of the crucial tools for human beings. The scientific study of language is called linguistics. When we study linguistics, we delve into semantics, which includes the study of figurative language. The objective of this study is to identify the types of figurative language in the lyrics of songs from the album